2009
DOI: 10.1038/nsmb.1700
|View full text |Cite
|
Sign up to set email alerts
|

The chaperonin TRiC blocks a huntingtin sequence element that promotes the conformational switch to aggregation

Abstract: Aggregation of proteins containing polyglutamine (polyQ) expansions characterizes many neurodegenerative disorders, including Huntington’s disease. Molecular chaperones modulate Huntingtin (Htt) aggregation and toxicity by an ill-defined mechanism. Here we determine how the chaperonin TRiC suppresses Htt aggregation. Surprisingly, TRiC does not physically block the polyQ tract itself, but rather sequesters a short Htt sequence element N-terminal to the polyQ tract, that promotes the amyloidogenic conformation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
375
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(408 citation statements)
references
References 50 publications
29
375
3
1
Order By: Relevance
“…The finding that exogenous ApiCCT1 r delivery can be taken up by cells and localizes to both the cytosol and nucleus are highly significant given that both compartments appear to contribute to pathogenic effects mediated by chronic mHTT expression (34), in particular nuclear accumulation of mHtt exerts toxic effects (1, 12, 17, 18). ApiCCT1 r may be directly interacting with mHtt to alter aggregation and toxicity, consistent with the previous finding that ApiCCT1 r can by itself suppress formation of insoluble mHtt aggregates and interacts with the first 17 amino acids of Htt, which regulates aggregation kinetics and other Htt functions (16). Given that toxicity is ameliorated in a cell model expressing full-length mHtt in which inclusions are not observed, it is likely that ApiCCT1 r exerts direct effects on mHtt-mediated phenotypes beyond interference with aggregation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The finding that exogenous ApiCCT1 r delivery can be taken up by cells and localizes to both the cytosol and nucleus are highly significant given that both compartments appear to contribute to pathogenic effects mediated by chronic mHTT expression (34), in particular nuclear accumulation of mHtt exerts toxic effects (1, 12, 17, 18). ApiCCT1 r may be directly interacting with mHtt to alter aggregation and toxicity, consistent with the previous finding that ApiCCT1 r can by itself suppress formation of insoluble mHtt aggregates and interacts with the first 17 amino acids of Htt, which regulates aggregation kinetics and other Htt functions (16). Given that toxicity is ameliorated in a cell model expressing full-length mHtt in which inclusions are not observed, it is likely that ApiCCT1 r exerts direct effects on mHtt-mediated phenotypes beyond interference with aggregation.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies demonstrated that overexpression of CCT1 can alter HD phenotypes in cell models of HD and that the apical subunit of yeast CCT1 (ApiCCT1 r ) alone interacts with recombinant mHtt in vitro and inhibits aggregation (15,16). Therefore, if exogenous delivery of ApiCCT1 r to cells could modulate intracellular aggregation and toxicity, the need for overexpression of the protein inside the cell would be circumvented and provide a rational option for delivery to the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRiC may play a role in suppressing Huntington's disease by decreasing huntingtin aggregate formation (Kitamura et al 2006;Tam et al 2009). If TRiC is to be used therapeutically in the clinic, it will be necessary to study human TRiC to further understand chaperonin functions inside human cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was shown that the first 17 amino acids in HTT, which adopt an α-helical conformation, can initiate the spontaneous aggregation of pathogenic polyQ tracts in cell-free assays (Thakur et al 2009). The importance of this polyQ flanking sequence for HTT misfolding is supported by biochemical studies with a chaperonin, which directly binds to the first 17 amino acids of HTT and blocks the de novo aggregation of N-terminal HTT fragments (Tam et al 2009). Thus, proteins that directly associate with polyQ flanking regions appear to strongly influence the spontaneous polymerization of disease proteins.…”
mentioning
confidence: 96%